Rapid Short and Medium Span Bridge Construction Using Innovative Precast Structural Systems - Scullion, Derek (My University, 2010)
The direct costs of bridge construction, such as materials, labor, and equipment are all well known. Recently however the indirect costs such as the cost of traffic disruptions, and construction safety are beginning to be factored into design decisions. These new considerations have led the Federal Highway Administration (FHWA) to explore Accelerated Bridge Construction (ABC), which is also known as a ?get in, get out, stay out? approach to bridge construction and replacement. Accelerated Bridge Construction is defined as replacement, or new bridge construction that uses design and construction methods to minimize impacts to the traveling public, river traffic, railroads, and the environment ? all while maintaining high levels of quality and safety. In other words, make bridge construction faster, and safer, while also making bridges last longer by using modern technology. This project focuses on one approach to ABC construction, using more precast elements, in an attempt to move towards an all precast bridge. Precast elements are fabricated offsite, in a controlled environment, and shipped to the project, where a crane is used to place them. Systems being examined in this project include precast stay?inplace forms for short to medium span bridges, and precast pile bent caps. Both of these systems can be used to dramatically reduce the amount of cast?in?place concrete on a typical bridge project. For the precast stay?in?place formwork system, this report first examines current practices of using precast concrete and bridges, and then identifies possible precast sections for further study in the proposed system. Double?T beam sections are identified for further study, next a series of analyses are run to identify a group of characteristics that would make a newly designed section more efficient. Using these characteristics, a new Channel section is designed, and analyzed against the Double?T section, the new section is found to offer a broader span range, and is designed to reduce several key 12 maintenance issues prevalent in adjacent member bridges. A list of recommendations for further study and discussion on this topic is included. Also included in this report is a construction study done on a bridge near Reynolds Wisconsin which used precast pile bent caps. The report follows the project from the precasting of the pile caps at County Materials in Roberts Wisconsin, to the placement and connection of caps to the piles, in Reynolds Wisconsin. Several problems were experienced with the construction process, and from these a list of recommendations for improvement was generated, and is included with the report.